Reviewing Factors of Audience Engagement in Live Streaming - Subiyakto, Aang; Yudhanta, Satya; Nurmiati, Evy; Utami, Meinarini Catur; Fetrina, Elvy; Sugiarti, Yuni; Hakiem, Nashrul; Huda, Muhammad Qomarul; Sangsawang, Thosporn (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2025)
Live streaming has become one of the most prominent digital phenomena in recent years, changing the way individuals interact, consume content and shop online. This study aims to identify and analyze the factors that influence audience engagement in live streaming, including audience motivation, the role of social interaction, technological features, platform distribution, and popular genres. Through a systematic literature review approach, 27 articles from relevant ScienceDirect and DOAJ databases were selected for analysis. The study results show that audience engagement is mainly influenced by parasocial interaction (PSI), entertainment-based motivation (hedonic value), and practical benefits (utilitarian value). Technologies such as live chat, gifting, and data-driven recommendation systems strengthen viewing duration and audience loyalty. In addition, platforms such as Twitch dominate the gaming and esports genres, while TikTok Live thrives in the e-commerce space. New genres such as VTubers and travel offer opportunities to attract a wider audience with avatar-based interaction approaches and virtual experiences. The research also identified gaps in the literature, including a lack of studies on local platforms, new genres, and the impact of innovative technologies such as AR/VR. This study makes an academic contribution by summarizing key findings and providing strategic guidance for platform developers, streamers and businesses in creating more engaging and effective live streaming experiences.